PERANCANGAN AKTIVITAS PEMASARAN UMKM PERCETAKAN MELALUI MEDIA KATALOG - Arie Indra Gunawan; Dinda Detia Nurul Falah; Mohammad Farid Najib (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This paper aims to increase knowledge about promotional media at small medium enterprises (SMEs). The project undertaken examines various variables regarding marketing communication and is applied to the product catalog as a communication medium. Product Catalog for SMEs is believed to be very meaningful because the condition of the printing sector of SMEs has not used this media much as a means of promotion and communication. This project is carried out through a qualitative research method through observation and interviews. Interviews were conducted with business actors, graphic design experts, and consumers. A literature review was carried out to complement the research data analyzed into three stages, namely; data collection, data processing, and data interpretation. The findings in this study state that consumers are greatly helped by the existence of a product catalog in their need for printing services. Other findings indicate that there are several important elements found as a complement to the catalog. Based on the results of the implementation of a cataloging project for SMEs, there are several elements in the catalog to become an effective medium in conveying information to consumers, including specific product information, proper design, comprehensive information, and capable of providing a positive image.